Computer Based Design and Manufacturing - Nasr, Emad Abouel; Kamrani, Ali K.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2007)
"Computer- Based Design and Manufacturing" offers insights into the methods and techniques that enable implementing a product design philosophy by integrating capabilities for intelligent information support and group decision-making utilizing a common enterprise network model and knowledge interface through shared technologies. This book offers a comprehensive overview of the latest methods and state-of-the-art technologies in intelligent product design. Including but not limited to: - Discussion of applied methods developed in field of the product design - Discussion on the need and solutions for new engineering paradigm and philosophy required for product design - Coverage of advances in information systems and technology in support of CFPD - Discussion of how to use web-based design environments "Computer-Based Design and Manufacturing" is a must have book for industrial engineers in both industry and academia who specialize in product development and supply chain management.
Product Design -- Product Development Life Cycle -- Product Life Cycle Cost Model -- Feature-Based Design and Tecniques -- Computer-Based Design and Features -- Methodologies of Feature Representations -- Feature Extraction Techniques -- Initial Graphics Exchange Specifications (IGES) -- Intelligent Feature Recognition Methodology -- Feature Interaction Methodology -- Feature-Based Process Planning and Techniques -- Mapping the Extracted Manufacturing Features to Process Planning -- Intelligent Feature Recognition Methodology (IFRM) Implementation -- Advanced Topics -- Rapid Prototyping -- Collaborative Engineering.
Keywords: Industrial engineering; Production engineering; Engineering design; Manufactures; Industrial and Production Engineering; Engineering Design; Manufacturing, Machines, Tools, Processes